2022
DOI: 10.1016/j.celrep.2021.110263
|View full text |Cite
|
Sign up to set email alerts
|

The ESCRT machinery directs quality control over inner nuclear membrane architecture

Abstract: SUMMARY The late-acting endosomal sorting complex required for transport (ESCRT) machinery has been implicated in facilitating the resealing of the nuclear envelope (NE) after mitosis, enabling compartmentalization of the genome away from the cytoplasm. Here, we leverage the stereotypic first division of the C. elegans embryo to identify additional functions of the ESCRT machinery in maintaining the structure of the inner nuclear membrane. Specifically, impaired ESCRT function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 87 publications
(138 reference statements)
0
15
0
Order By: Relevance
“…The endosomal sorting complex required for transport machinery facilitates resealing of the NE after NERs, but also directs quality control of INM morphology by pruning INM invaginations. 37 It is known that NER repair by the endosomal sorting complex required for transport-III complex depends, among other factors, on the appropriate interaction of LEMD2 and BAF, 38 which in our case was at least modulated, if not disrupted due to the p.L13R mutation located in the LEM-domain (Figure 6A). Therefore, we propose that the disturbed binding of both proteins impairs NER repair capacity, which is particularly important in tissues such as the heart, which is exposed to mechanical forces throughout life and increased stiffness with aging.…”
Section: Discussionmentioning
confidence: 51%
“…The endosomal sorting complex required for transport machinery facilitates resealing of the NE after NERs, but also directs quality control of INM morphology by pruning INM invaginations. 37 It is known that NER repair by the endosomal sorting complex required for transport-III complex depends, among other factors, on the appropriate interaction of LEMD2 and BAF, 38 which in our case was at least modulated, if not disrupted due to the p.L13R mutation located in the LEM-domain (Figure 6A). Therefore, we propose that the disturbed binding of both proteins impairs NER repair capacity, which is particularly important in tissues such as the heart, which is exposed to mechanical forces throughout life and increased stiffness with aging.…”
Section: Discussionmentioning
confidence: 51%
“…Additionally, upon closer inspection of control embryos, we found that Lgd associates weakly with the periphery of the nucleus as the nuclear envelope begins to disassemble ahead of each mitotic division ( Figure 3, B and C ). We speculated that exposure to CHMP7, which we demonstrated previously to localize to the inner nuclear membrane during interphase in C. elegans embryos ( Shankar et al. , 2022 ), enables transient recruitment of Lgd during nuclear envelope breakdown.…”
Section: Resultsmentioning
confidence: 91%
“…High-pressure freezing was carried out using a Leica EM ICE system. After freezing, samples were substituted into a solution of 1% OsO 4 and 1% H 2 O in acetone, as described previously ( Shankar et al. , 2022 ), followed by centrifugation into increasing concentrations of epoxy EMbed 812 resin (Electron Microscopy Sciences, Hatfield, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Curiously, although Chm7/CHMP7 is actively exported from the nucleus in budding yeast and human cells, in C. elegans , it is constitutively found at the INM, bound to at least two LEM-domain integral INM proteins ( Shankar et al, 2022 ). Thus, binding to LEM proteins might not activate Chm7/CHMP7 polymerization as it does in yeast and mammals.…”
Section: Inm Pruningmentioning
confidence: 99%
“…In fact, in these model systems, allowing Chm7/CHMP7 to bind Heh1/LEM2 in the nucleus drives the formation of a network of fenestrated INM cisterna that are likely deleterious to cell viability ( Thaller et al, 2019 ; Vietri et al, 2020b ). In contrast, similar but morphologically distinct tubular INM extensions are also described in C. elegans , but in this case, they are a product of CHMP7 loss, not gain, of function ( Shankar et al, 2022 ). The implication is that CHMP7 is required to prune these INM tubules, which might be a byproduct of NE reformation mechanisms at the end mitosis ( Penfield et al, 2020 ).…”
Section: Inm Pruningmentioning
confidence: 99%